ChemInform Abstract: An Approach to Alicyclic Ring‐Fused Xanthines. Issue 9 (5th March 2013) - Liubchak, Kostiantyn; Tolmachev, Andrey; Grygorenko, Oleksandr O.; Nazarenko, Kostiantyn
Abstract A convenient three‐step sequence allows the synthesis of the title compounds (V), which are of interest in drug discovery, via reaction of 6‐aminouracils with lactam derivatives (II), bromination, and copper‐catalyzed arylation.